Meningoencephalitis in intensive care unit: Do Japanese Encephalitis cases go unsuspected? - Ghimire, Ashish; Bhattarai, Balkrishna; Khanal, Basudha; Marhatta, Suchana; Deo, Gopendra Prasad (Journal of Chitwan Medical College, 2017)
Background: Meningoencephalitis (ME) is a medical emergency. Acute infective encephalitis is usually viral. Nepal has the second highest prevalence of JE in South East Asia. About one third of the JE cases results in death. The records of the JE in the laboratory of B.P. Koirala Institute of Health Sciences (BPKIHS) showed 760 samples to have the evidence of JE infection out of 3352 tested during the period of 2001-2011 AD. The present study aimed to conduct an audit on meningoencephalitis cases admitted in the ICU of our hospital in an attempt to find its burden. Methods: Medical records of all the adult patients with the provisional diagnosis of Meningoencephalitis at BPKIHS over the period of 2009-2011 AD were examined. Laboratory findings of all the patients diagnosed with ME who were admitted to the eight bedded general intensive care unit (ICU) were also reviewed. The diagnosis was made based on the findings of medical history, clinical examination and cerebrospinal fluid analysis for biochemistry and cytology, results of anti JE IgM test performed on CSF and/or serum. Results: Altogether 127 samples of CSF were obtained from adult patients admitted in different inpatient department of BPKIHS with the clinical diagnosis of meningo encephalitis between 2009-2011 AD. Out of them, 25 (19.68%) were tested positive of JE. A total of 684 patients were admitted over the same period with different diagnoses in 8 bedded ICU of hospital. Fifteen (2.19%) were transferred to the ICU with the ME. In the ICU, 9(60%) were treated as viral encephalitis. Among them CSF of only 4 patients’ were sent for testing for JE and found positive in 2 cases. Seven (46.6%) patients expired while 4(26.6%) were taken home by the relatives against medical advice in critically ill conditions and remaining 4 (26.6%) improved and transferred to ward. Among the expired patients 5 (71.4%) had viral encephalitis. Conclusion: JE is a real problem but many cases are likely to have been gone undetected. Adoption of a more intensive approach with much liberal serology testing policy seems to be appropriate for better detecting JE cases in the setting.